2013
DOI: 10.4049/jimmunol.1202610
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation Induced by MMP-9 Enhances Tumor Regression of Experimental Breast Cancer

Abstract: Matrix metalloproteinases (MMPs) have been suggested as therapeutic targets in cancer treatment, but broad-spectrum MMP inhibitors have failed in clinical trials. Recent data suggest that several MMPs including MMP-9 exert both pro- and antitumorigenic properties. This is also the case of the natural inhibitors of MMPs, tissue inhibitor of metalloproteinases (TIMPs). The inhibitor of MMP-9 is TIMP-1, and high levels of this enzyme have been associated with decreased survival in breast cancer. Inflammation is o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 55 publications
1
63
0
1
Order By: Relevance
“…Massive infiltration of neutrophils may elicit a direct cytotoxic effect by releasing hydrogen peroxide, leading to tumor regression, whereas a low-grade neutrophil gradient is tumor progressive (38,39). This is in line with our present data showing that addition of a high number of neutrophils caused a disintegration of mammospheres in vitro.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Massive infiltration of neutrophils may elicit a direct cytotoxic effect by releasing hydrogen peroxide, leading to tumor regression, whereas a low-grade neutrophil gradient is tumor progressive (38,39). This is in line with our present data showing that addition of a high number of neutrophils caused a disintegration of mammospheres in vitro.…”
Section: Discussionsupporting
confidence: 83%
“…Neutrophils possess dual roles in cancer progression depending on their phenotype or number in the tumor microenvironment (38,39). Massive infiltration of neutrophils may elicit a direct cytotoxic effect by releasing hydrogen peroxide, leading to tumor regression, whereas a low-grade neutrophil gradient is tumor progressive (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Similar dependence of infiltrating macrophages on MMP-9 and its proteolytic activity is manifested in plasminogen-knockout mice, where supplementation of active MMP-9 was shown to restore impaired macrophage influx (Gong et al, 2008). In support of the notion that intratumoral MMP-9 can locally regulate influx and presentation of leukocytes in developing tumors, it was demonstrated that the adenovirus-mediated induction of MMP-9 in breast cancer xenografts dramatically altered their cytokine profile and enhanced production of neutrophil chemoattractants, KC and MIP-2, leading to a massive neutrophil infiltration (Leifler et al, 2013). …”
Section: Tumor-associated Leukocytes and Their Mmp-9 In Vegf-inducmentioning
confidence: 96%
“…Inflammation is a hallmark of cancer. An MMP-9/TIMP-1 imbalance is also observed in cancers (33). The balance between MMP-9 expression and TIMP-1 expression may be an important indicator of tumor progression and may be useful as a predictor of tumor recurrence (34).…”
Section: )mentioning
confidence: 99%